2012
DOI: 10.1002/app.36468
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of peanut shell powder as a novel filler in natural rubber

Abstract: This work focuses on the use of peanut shell powder (PSP) as filler in natural rubber (NR). Peanut, one of the food crops in the world, generates large amounts of waste namely peanut shell. Modified and unmodified PSP‐NR composites with varying particle size and dosages were prepared by an open mill mixing technique. The processing characteristics and the curing behavior of the composites were determined by Monsanto Rheometer. The technological performance was done by analyzing the tensile strength, tear stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…This had shown to have good emulsifying properties and hence had potential to find applications in emulsified foods and could be a useful food ingredient. Moreover, coconut and peanuts shell powder could be used as filler in natural rubber (Sareena et al, 2012a(Sareena et al, , 2012b. Papaya processing wastes showed new and interesting potential applications compared to those of previous studies.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…This had shown to have good emulsifying properties and hence had potential to find applications in emulsified foods and could be a useful food ingredient. Moreover, coconut and peanuts shell powder could be used as filler in natural rubber (Sareena et al, 2012a(Sareena et al, , 2012b. Papaya processing wastes showed new and interesting potential applications compared to those of previous studies.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…NR/MC biocomposites were characterized by lower values of scorch time and optimal cure time comparing to unfilled NR, NR/WB and NR/WF biocomposites. This is due to small size particles of MC, which allows good dispersion of biofiller into NR matrix and improves interactions between cellulosic filler surface and NR matrix (Sareena et al 2012b). It was observed that increasing content of MC filler in biocomposites decreases scorch time and increases optimal cure time.…”
Section: Curing Characteristicsmentioning
confidence: 99%
“…Up to now there are not many works focused on the use of peanut shell as filler in polymer matrices. Sareena et al 22 evaluated the mechanical properties of composite materials based on a natural rubber matrix with peanut shell fillers. The study was focused on the effect of the particle size and the previous alkaline treatment on final performance of composites.…”
Section: Introductionmentioning
confidence: 99%